2014
DOI: 10.1016/j.parkreldis.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a formal exercise program on Parkinson's disease: A pilot study using a delayed start design

Abstract: Introduction Parkinson’s Disease (PD) is a progressive neurodegenerative disease. Increasing evidence shows that physical exercise is beneficial for motor and non-motor symptoms of PD, and animal models suggest that it may help slow progression of disease. Methods Using a randomized delayed-start design, 31 patients were randomized to an early start group (ESG) or a delayed start group (DSG) exercise program. The ESG underwent a rigorous formal group exercise program for 1 h, three days/week, for 48 weeks (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 27 publications
0
37
0
1
Order By: Relevance
“…Indeed, work suggests that exercise in early Parkinson’s disease can elevate striatal dopamine D2 receptor binding potential and normalize corticomotor excitability (Fisher, et al, 2013, Fisher, et al, 2008). Furthermore, a recent study by Park et al reported a greater efficacy for early versus delayed exercise intervention with regards to depressive symptoms, though not for ratings on the Unified Parkinson’s Disease Rating Scale (UPDRS) (Park, et al, 2014). Our animal model was more relevant to early stage than late stage PD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, work suggests that exercise in early Parkinson’s disease can elevate striatal dopamine D2 receptor binding potential and normalize corticomotor excitability (Fisher, et al, 2013, Fisher, et al, 2008). Furthermore, a recent study by Park et al reported a greater efficacy for early versus delayed exercise intervention with regards to depressive symptoms, though not for ratings on the Unified Parkinson’s Disease Rating Scale (UPDRS) (Park, et al, 2014). Our animal model was more relevant to early stage than late stage PD.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial improvement in depressive symptoms has been noticed in case of a group of patients that started with exercise earlier than another group [43]. The importance of this discovery lies in the fact that mood can often have a more decisive impact on quality of life with PD than the physical disorder itself.…”
Section: Depressionmentioning
confidence: 95%
“…Such studies encompass a range of randomized controlled trials including, for example, pharmaceutical trials [50,51], surgical trials [52,53], nonpharmaceutical therapy trials [54,55] and clinical practice trials [56,57]. Additionally, the measure has been extensively used in descriptive surveys including, for example, studies relating to mood [58,59], nutrition [60,61], exercise [62,63] and personality style [64,65].…”
Section: Examples Of Prominent and Widely Used Proms In Selected Neurodmentioning
confidence: 99%